Simulation and prediction of land use in urban agglomerations based on the PLUS model: a case study of the Pearl River Delta, China - Gong, Jing; Du, Hongyan; Sun, Yong; Zhan, Yun (Frontiers in Environmental Science, 2023)
The Pearl River Delta (PRD) is a highly urbanized region in China that faces significant challenges in land use management. These challenges include the decrease in agricultural and ecological land resulting from rapid urbanization, the effectiveness of government governance, and the trajectory of development, all of which warrant careful research examination. Moreover, existing studies on land use in the PRD predominantly rely on static historical analysis, lacking a multi-scenario simulation approach. This study examines land use in PRD using a Patch-Generating Simulation (PLUS), from 1985 to 2020 to address this gap. Three scenarios were established to simulate potential land use outcomes in the PRD by 2030: spontaneous change, cropland protection, and ecological protection. The findings reveal that cropland, forest, and impervious surfaces are the dominant land use types in the PRD. From 1985 to 2020, the proportion of cropland decreased from 37.63% to 27.40%, with most conversions occurring to impervious surfaces and forest land. The proportion of impervious surfaces increased from 1.81% to 12.57%, primarily from conversions of cropland, forest, and water bodies. Economic development, population growth, accessibility, climatic factors, and topographic conditions were shown to be the primary determinants of land use in the PRD. Modelling results suggest that under the spontaneous change scenario, cropland and ecological land decrease, while impervious surfaces expand significantly, threatening cropland preservation and ecological construction. However, under the cropland protection scenario, the conversion rate of cropland to other land types can be effectively controlled, contributing to efficient preservation. Under the ecological protection scenario, impervious infrastructure encroachment on ecological land can be mitigated, but cropland protection is limited. The study proposes cropland protection and ecological priority policies to optimize the structure of land use, enhance efficiency, and offer policy guidance for the efficient utilization of land resources and the preservation of the ecological environment in the PRD.